Resource Based View (RBV) in Improving Company Strategic Capacity - Nurul Wardani Lubis (LifeSciFi, 2022)
The growth of the industrial sector that continues to grow requires companies to have high competitiveness capabilities. Companies in order to survive in intensive competition and remain competitive with other companies are required to be able to innovate. One internal approach that can be used to create competitive advantage is to use a Resource Based View (RBV). This Resource Based View (RBV) method examines a company's assets, expertise, capabilities, and intangible assets, including the internal resources of the company, and determines its strategic advantage. The Resource Based View (RBV) approach highlights a company's capabilities and resources that are unique to that company and adds significant value for the company. Using the Resource Based View (RBV) theory which focuses on the resources owned by the company and its capabilities can provide an appropriate theoretical perspective for examining how internal factors can become resources to generate competitive advantage to increase the company's strategic capacity. Establishing a framework with a Resource Based View (RBV) approach for companies is expected to provide the right framework to have high competitiveness for companies originating from the management and use of company capacities and resources.